Toxicity patterns of novel PI3K combinations in patients with non-Hodgkin lymphoma. Issue 3 (23rd February 2021) - Rodgers, Thomas D.; Williams, AnnaLynn M.; Baran, Andrea; Reagan, Patrick M.; Casulo, Carla; Zent, Clive S.; Evans, Andrew; Friedberg, Jonathan W.; Barr, Paul M.
Abstract: Phosphoinositide-3-kinase (PI3K) inhibitors have efficacy in lymphoid malignancies; however, inflammatory and infectious toxicities can compromise the treatment course. An improved understanding of these toxicities will guide clinical use and further development. We evaluated the occurrence of treatment-related adverse events (AEs) in a retrospective review of 79 patients treated in standard fashion with PI3K inhibitor monotherapy or with anti-CD20 monoclonal antibodies or as part of a novel combination regimen. Patients treated with a novel combination were at a higher risk of developing a severe AE compared to those treated with standard therapy (HR 1.89, 95% CI 1.02, 3.49; p = .04). Additionally, previously untreated patients were at higher risk of developing a severe AE compared to previously treated patients (HR 3.19, 95% CI 1.48, 6.84; p = .003). These results caution against the use of untested PI3K inhibitor combinations in routine practice and suggest that early phase clinical trials should utilize conservative treatment schemas.